2000
DOI: 10.1108/09615530010359120
|View full text |Cite
|
Sign up to set email alerts
|

Mixed convection in a square cavity due to heat generating rectangular body

Abstract: Flow in the cavity with heat generating body finds wide domestic and industrial applications. The heat transfer characteristics and the irreversibility generated in the cavity depend on mainly the cavity size, aspect ratio of the heat generating body, and inlet/exit port locations. In the present study, effect of exit port locations on the heat transfer characteristics and irreversibility generation in a square cavity with heat generating body is investigated. A numerical simulation is carried out to predict t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…They concluded that both the heat transfer coefficient and the dimensionless temperature in the body center strongly depend on the configurations of the system. Shuja et al [4] numerically studied mixed convection in a square cavity due to a heat generating rectangular body and investigated the effect of exit port locations on the heat transfer characteristics and irreversibility generation in the cavity. They showed that the normalized irreversibility increased as the exit port location number increased and the heat transfer from the solid body was enhanced while the irreversibility was reduced.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that both the heat transfer coefficient and the dimensionless temperature in the body center strongly depend on the configurations of the system. Shuja et al [4] numerically studied mixed convection in a square cavity due to a heat generating rectangular body and investigated the effect of exit port locations on the heat transfer characteristics and irreversibility generation in the cavity. They showed that the normalized irreversibility increased as the exit port location number increased and the heat transfer from the solid body was enhanced while the irreversibility was reduced.…”
Section: Introductionmentioning
confidence: 99%
“…For this geometry, the authors performed a series of computations covering a rather wide range of Strouhal numbers (from 0.1 to 10) and they report that, in all cases, heat transfer is enhanced when inlet flow oscillation is enforced. Steady mixed convection inside a cavity where a heated rectangular cylinder is present has been analysed by Shuja et al [11]. In particular, these authors focussed on the influence of the heated body size and the position of the exit port.…”
Section: St Tmentioning
confidence: 99%
“…The authors investigated the effect of varying Rayleigh number with a fixed inlet mass flow rate on the overall cooling effectiveness. Shuja et al [2] investigated two-dimensional mixed convection of air in a square cavity with a single heat generating body. In that study, the effects of cavity exit-port locations on heat transfer and entropy generation for two body aspect ratios were considered.…”
Section: Introductionmentioning
confidence: 99%